Suppressive Effect of Caffeic Acid and its Derivatives on the Generation of UVA-induced Reactive Oxygen Species in the Skin of Hairless Mice and Pharmacokinetic Analysis on Organ Distribution of Caffeic Acid in ddY Mice - Yamada, Yumiko; Yasui, Hiroyuki; Sakurai, Hiromu (Photochemistry and photobiology, 2006)
Caffeic acid (CA) and its analogues such as rosmarinic acid are well known as antioxidative agents. Exposure to UVA is known to generate reactive oxygen species (ROS) such as singlet oxygen (1O2) and superoxide anion radical (·O2−) in the skin of animals, which in turn induces skin photodamage and photoaging. Because CA and its analogues quench 1O2, these compounds were topically applied to the abdominal skin of live hairless mice and were found to suppress ROS generation upon UVA exposure. Furthermore, the generation of UVA-induced ROS was also suppressed in the skin of mice that were orally given CA. In order to understand the mechanism by which CA blocks ROS production in UVA-exposed skin, the pharmacokinetics of CA upon oral administration to mice was followed and CA was found to efficiently distribute in the skin. These results suggest that skin damage by UVA-induced ROS generation is reduced by oral supplementation of CA, which has a scavenging and quenching activity against ROS.